Correlation between structural and catalytic properties of copper supported on porous alumina for the ethanol dehydrogenation reaction - Cassinelli, Wellington H. [UNESP]; Martins, Leandro [UNESP]; Passos, Aline R. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Rochet, Amelie [UNESP]; Briois, Valerie; Santilli, Celso V. [UNESP] (Wiley-Blackwell, 2015)
Structural and surface features of highly dispersed copper catalysts supported on hierarchical porous alumina were evaluated for the ethanol dehydrogenation reaction. The catalysts were prepared by incipient wetness impregnation of alumina obtained by a dual template sol-gel procedure. Structural characterizations provided evidence that the copper was highly dispersed on the alumina in the form of monomeric octahedral Cu2+ species adsorbed into an incomplete layer. A two-step reduction was observed for the catalysts in a temperature range of 50-250 degrees C under H-2/He flow. The temperature for onset of reduction and the percentage of Cu+ species formed upon activation were dependent on the Cu loading. At lower Cu loadings, the amount of Cu+ increased, leading to a slower and less complete reduction. Based on the apparent activation energy and turnover frequency, it could be concluded that Cu+ containing a mixture of Cu+/Cu-0 results in a more efficient catalyst than Cu-0 for the ethanol dehydrogenation reaction.
Keywords: Copper; Dehydrogenation; Supported catalysts; Time-resolved spectroscopy; X-ray absorption spectroscopy